1988
DOI: 10.1063/1.866691
|View full text |Cite
|
Sign up to set email alerts
|

Theory and simulation of electromagnetic beam modes and whistlers

Abstract: Using particle-in-cell simulations and analytical methods, a study of the nonlinear evolution of electromagnetic instabilities driven by an anisotropic electron beam (Tb⊥≫Tb∥) in an external magnetic field is performed. The unstable waves are either whistlerlike or beam-mode-like depending on the external field strength and beam velocity. The evolution of the particle distribution differs significantly in the two regimes. Even in the presence of a faster electrostatic instability, the electromagnetic waves gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Previous electromagnetic simulations of the electron/electron configuration have not addressed this issue. Newman et al 11 and Winglee et al 12 considered initially anisotropic electron beams which excited the intrinsically electromagnetic electron anisotropy instability. Yin et al, 9 Newman et al, 11 and Nambu et al 13 considered only e Ͼ 1 where ͑as we shall demonstrate͒ electromagnetic effects of the electron/electron beam instability are relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Previous electromagnetic simulations of the electron/electron configuration have not addressed this issue. Newman et al 11 and Winglee et al 12 considered initially anisotropic electron beams which excited the intrinsically electromagnetic electron anisotropy instability. Yin et al, 9 Newman et al, 11 and Nambu et al 13 considered only e Ͼ 1 where ͑as we shall demonstrate͒ electromagnetic effects of the electron/electron beam instability are relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies, [21][22][23] which assume a weaker, faster, and more anisotropic beam, showed a stronger interaction between the electrostatic beam instability and the oblique beam-whistler instability that left the beam more nearly isotropic and less susceptible to the growth of parallel whistler waves (and thus less further pitch-angle scattering of the beam) at late times. Using a different set of parameters (stronger, slower and higher beta), Newman et al 16 found weaker growth of the electrostatic mode and thus larger residual beam temperature anisotropy that drive stronger parallel whistler waves and thus more pitch-angle scattering of the beam.…”
Section: -9mentioning
confidence: 99%
“…Newman et al 16 assumed a relatively dense beam ($10%) at low velocities where the electrostatic mode was suppressed or only weakly unstable. The excited whistler waves (parallel modes only in their 1-D simulation) modified the beam distribution function by pitchangle scattering so that the energetic tail of the beam could excite secondary electrostatic waves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations